2000
DOI: 10.1095/biolreprod62.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Mobility: Phenotype in Roosters (Gallus domesticus) Determinedby Concentration of Motile Sperm and Straight Line Velocity1

Abstract: Previous research demonstrated that sperm mobility, i.e., the net movement of a sperm population, is a quantitative trait of the domestic fowl. However, the cellular basis for this trait was unknown. In the present work, individual motile sperm were evaluated with a Hobson SpermTracker in order to identify one or more properties of motile sperm that could account for variation in sperm mobility observed among males. A method was validated for assessing sperm motion over an erythrocyte monolayer at body tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 9 publications
3
48
0
Order By: Relevance
“…Computer-assisted sperm motion analysis was performed as outlined by Froman and Feltmann (2000) using 10 replicate roosters. Reagents were purchased from Sigma-Aldrich, St. Louis, MO.…”
Section: Methodsmentioning
confidence: 99%
“…Computer-assisted sperm motion analysis was performed as outlined by Froman and Feltmann (2000) using 10 replicate roosters. Reagents were purchased from Sigma-Aldrich, St. Louis, MO.…”
Section: Methodsmentioning
confidence: 99%
“…We also recorded the number of sperm cells detected by the CASA plug-in because moving sperm are likely to interfere more with each other at higher densities, a parameter we could not control. Sperm velocity has previously been described using VSL, VAP, or VCL or a combination of these parameters (Holt et al 1997;Froman and Feltmann 2000;Gage et al 2004;Pizzari et al 2004). In our samples, these parameters were strongly correlated with each other (r, 0.93-0.998; all P<0.0001).…”
Section: Sperm Velocity and Sperm Longevitymentioning
confidence: 99%
“…Sperm quality measured as 'sperm mobility', an in vitro assay which measures the ability of sperm to penetrate a solution of an inert medium Froman and Feltmann, 2000). Sperm mobility is a normally distributed trait which is stable and significantly repeatable within males Froman and Feltmann, 2000).…”
Section: Post Insemination Strategies Malesmentioning
confidence: 99%
“…Sperm quality measured as 'sperm mobility', an in vitro assay which measures the ability of sperm to penetrate a solution of an inert medium Froman and Feltmann, 2000). Sperm mobility is a normally distributed trait which is stable and significantly repeatable within males Froman and Feltmann, 2000). An artificial insemination experiment where the same number of sperm from a male with average-, and from a male with high-sperm mobility were mixed and artificially inseminated into the same female revealed that, when competing with low mobility ejaculates of the same size, high mobility ejaculates fertilised a disproportionate number of eggs (Birkhead et al, 1999).…”
Section: Post Insemination Strategies Malesmentioning
confidence: 99%